Competências profissionais do bacharel em educação física: a noção dos docentes que atuam na formação inicial do estado do Paraná - Albino, Renata Leila (2012)
The general aim of this study was to investigate the general concept of professional competence of faculty who teach in Physical Education Bachelor courses, in the state of Paraná, from the knowledge that underlie professional intervention. The methodological approach was based on descriptive qualitative research. To gather information, we used a questionnaire in Likert scale (range: 1 - 5) and three open response questions, developed with the focal group technique and the literature consulted. The selection of HEIs and faculty followed the guidelines of probabilistic sampling, considering those HEIs which are accredited by MEC and that offer the Bachelor degree in Physical Education, and the faculty graduated in the area and acting in the bachelor courses. The study included 132 faculty attached to 19 accredited HEIs. The Student's t test and repeated measures ANOVA were used for data analysis and comparisons. The results highlighted the importance that the faculty attribute the following types of Knowledge: a) Declarative/Conceptual, from biology, motor development and human behavior, focused on teaching and learning and derived from scientific research, in contrast to the body expressions /manifestations and understanding/insertion of man in society; b) Procedure, which includes the skills that facilitate the organization of theoretical knowledge for its transmission; c) Attitudinal, which brings together the motivational, perceptual and cognitive processes of the individual, behavior, conducts and choices, his beliefs and representations. The Attitudinal Knowledge stood among the others, highlighting the concern of faculty with: a) the subjective aspects of intervention and individual characteristics, contexts and populations; b) the proposals and/or applications to the students/clients/users; c) in detriment to the overvaluation of practical and conceptual knowledge. In the research themes, the knowledge oriented to project development, equipment and patents for different spaces, areas and populations, was highlighted. However, the search for up-to-date knowledge occur through: a) the participation in scientific events in the area, study/research groups and technical courses; b) using the Internet to access scientific papers/journals and books; c) the appropriation of knowledge from other fields, such as psychology and sociology; d) consultation and/or indication of national/international journals in the area and evaluated by the Qualis CAPES, indicating the focus of the faculty to the knowledge of scientific nature, subject to the scrutiny of institutions and representativity among the scientific community.